Analysis of serum levels of cytokines, chemokines, growth factors, and monoamine neurotransmitters in patients with tick-borne encephalitis: identification of novel inflammatory markers with implications for pathogenesis - Palus, Martin; Formanová, Petra; Salát, Jiří; Žampachová, Eva; Elsterová, Jana; Růžek, Daniel (Journal of medical virology, 2015)
Tick-borne encephalitis (TBE) is a leading human neuroinfection in Europe and northeastern Asia. However, the pathophysiology of TBE is not understood completely. This study sought to determine the specific serum mediators that are associated with acute TBE. The levels of 30 cytokines, chemokines, and growth factors were measured in serum samples from 87 patients with clinically and serologically confirmed acute TBE and from 32 control subjects using the Cytokine Human Magnetic 30-Plex Panel for the Luminex platform. Serum levels of the monoamine neurotransmitters serotonin, dopamine, and noradrenaline were measured via enzyme-linked immunosorbent assay. TBE virus infection elicited increased levels of the pro-inflammatory cytokines interleukin (IL)-6, IL-8, and IL-12. TBE patients had higher IL-12:IL-4 and IL-12:IL-10 ratios than control patients, reflecting the global pro-inflammatory cytokine balance. Serum levels of the monoamine neurotransmitters serotonin, dopamine, and noradrenaline were significantly lower in TBE patients than in the control group. Most interestingly, increased levels of hepatocyte growth factor and vascular endothelial growth factor were observed in TBE patients; these proteins may be novel and mechanistically important inflammatory biomarkers of TBE.
Keywords: Humans; lidé středního věku; neurotransmiterové látky; Encephalitis, Tick-Borne; klíšťová encefalitida; dítě; Child; cytokiny; Female; Aged; mladý dospělý; dospělí; Neurotransmitter Agents; neuroinfection; senioři; lidé; Biogenic Monoamines; Intercellular Signaling Peptides and Proteins; Serum; předškolní dítě; Adult; tick-borne encephalitis virus; neuroinflammation; ženské pohlaví; mezibuněčné signální peptidy a proteiny; Male; Middle Aged; Immunoassay; sérum; Adolescent; Cytokines; Aged, 80 and over; Young Adult; senioři nad 80 let; mužské pohlaví; imunoanalýza; Child, Preschool; luminex; biogenní monoaminy; mladiství